1987
DOI: 10.1002/bip.360261005
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic models for water–protein sorption hysteresis

Abstract: SynopsisSorption isotherms of water by proteins show hysteresis that appears to be due to interactions at the molecular level. Four thermodynamically consistent models for this irreversible process are presented. Hysteresis could be the result of slow, incomplete conformational changes occurring upon addition and removal of water. Conformational hysteresis would occur if a number of different conformations, each corresponding to a local free energy minimum, could be present at each pressure of water vapor. Hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…It is known that protein sorption isotherms exhibit hysteresis below a w 0.9 (27)(28)(29)(30)(31). For a given a w , proteins are typically more hydrated during desorption than absorption.…”
Section: Vapor Sorption On Lyophilized and Dried Microbead Samplesmentioning
confidence: 99%
“…It is known that protein sorption isotherms exhibit hysteresis below a w 0.9 (27)(28)(29)(30)(31). For a given a w , proteins are typically more hydrated during desorption than absorption.…”
Section: Vapor Sorption On Lyophilized and Dried Microbead Samplesmentioning
confidence: 99%
“…Lillford (1988) has expressed a similar opinion, crediting (as others had previously [Levine and Slade, 1986]) the onset of enzymatic activity in lowmoisture, amorphous lysozyme powders to plasticization by sorbed water, leading to sufficient segmental mobility for diffusion-limited enzyme-substrate interactions to occur. With regard to water-protein sorption hysteresis, Bryan (1987b) has suggested that hysteresis "could result from slow, incomplete conformational changes occurring upon addition of water" to proteins in the solid state, and its subsequent removal. These changes could result from incomplete "intermolecular phase annealing" or "phase changes," and the resulting hysteresis "might be related to the physical state and prior history of the sample" (Bryan, 1987b).…”
Section: Water Vapor Sorption By Glassy and Rubbery Polymersmentioning
confidence: 99%
“…With regard to water-protein sorption hysteresis, Bryan (1987b) has suggested that hysteresis "could result from slow, incomplete conformational changes occurring upon addition of water" to proteins in the solid state, and its subsequent removal. These changes could result from incomplete "intermolecular phase annealing" or "phase changes," and the resulting hysteresis "might be related to the physical state and prior history of the sample" (Bryan, 1987b). Again, Lillford (1988) has expressed similar sentiments, pointing out (again as others had previously [Levine and Slade, 1987]) that starch (van den Berg, 1981) and other hydrophilic polymers plasticized by water "are far from inert in the adsorption process," should not be modeled as "an immobile and unaffected substrate," manifest a "nonequilibrium desorption process responsible for hysteresis," and probably are "usually in a metastable kinetic state ... where the interaction of polymers and water cannot be treated in terms of equilibrium thermodynamics."…”
Section: Water Vapor Sorption By Glassy and Rubbery Polymersmentioning
confidence: 99%
See 2 more Smart Citations